Internalization of Islamic Religious Education for Children of Broken Home Victims - Rahmayanti Siregar (Sufiya Journal of Islamic Studies, 2023)
This study aims to explore the implementation of Islamic religious education in broken home families and parents' efforts in teaching religious values to their children. Through a qualitative approach with interviews with several mothers from broken home families, this study identified various efforts made by parents in instilling Islamic religious education. The findings show that despite emotional challenges and limited resources, parents still try to teach Islamic religious education through examples of good behavior and activities such as prayer, Quran recitation, and the cultivation of noble morals. The findings also reveal the importance of parents' emotional support and consistency in educating their children, especially in situations where the family is not intact.